2009
DOI: 10.1093/bja/aep018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenylephrine on the sublingual microcirculation during cardiopulmonary bypass

Abstract: Our data demonstrate that an increased perfusion pressure produced by phenylephrine at constant CPB flow may decrease microcirculatory blood flow in the sublingual mucosal microcirculation due to microvascular blood flow shunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 27 publications
1
35
0
4
Order By: Relevance
“…50,51 Indeed, a 20-mmHg increase in systemic blood pressure by phenylephrine was associated with depressed sublingual smallvessel blood flow while medium-sized vessels were unaffected. 52 However, from this study, it was unclear whether this increase in blood pressure also was associated with augmentation of cardiac output. Others showed an increase in local gastric mucosal blood flow after dopamine infusion, whereas systemic flow remained stable.…”
Section: Blood Pressure and Cardiac Outputmentioning
confidence: 70%
See 1 more Smart Citation
“…50,51 Indeed, a 20-mmHg increase in systemic blood pressure by phenylephrine was associated with depressed sublingual smallvessel blood flow while medium-sized vessels were unaffected. 52 However, from this study, it was unclear whether this increase in blood pressure also was associated with augmentation of cardiac output. Others showed an increase in local gastric mucosal blood flow after dopamine infusion, whereas systemic flow remained stable.…”
Section: Blood Pressure and Cardiac Outputmentioning
confidence: 70%
“…[80][81][82] In contrast, Maier et al demonstrated that initiation of CPB did not alter sublingual microcirculatory perfusion, while an additional phenylephrine-induced systemic blood pressure increase reduced small vessel blood flow and augmented tissue hemoglobin oxygenation. 52 Others showed that the rectal microvascular flow index and the proportion of perfused vessels was almost normal at 30 minutes following cardiac surgery. 23…”
Section: Cardiac Surgery With Cardiopulmonary Bypassmentioning
confidence: 99%
“…Of all patients, 54% required at least one postoperative hemodialysis (median 1, range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Grafts with delayed function had a longer Cit (mean 11 h 36 min) compared with those not requiring any postoperative hemodialysis (mean 7 h 45 min)(P < 0.05).…”
Section: Postoperative Kidney Functionmentioning
confidence: 98%
“…Cela dit, la même équipe, en randomisant les patients à recevoir initialement soit de la phényléphrine, soit de la noradrénaline, ne retrouve pas de différence entre les deux groupes concernant les mêmes paramètres [39]. Chez des patients hémodynamiquement stables après pontage aortocoronaire, le MFI capillaire sublingual est abaissé après traitement par phényléphrine, malgré une augmentation de la saturation tissulaire en oxygène (StO 2 ) [NIRS), et une accé-lération du débit sanguin microcirculatoire est mesurée en laser échographie-doppler évoquant l'aggravation d'un shunt microcirculatoire [40].…”
Section: Phényléphrineunclassified
“…Phényléphrine -Aggravation clairance ICG, clairance créatinine, lactate, dans une étude en crossing-over avec la noradrénaline [38] -Pas de modification dans une étude randomisée [39] -Aggravation de l'indice de flux microcirculatoire [40] Noradrénaline -Amélioration non significative de la proportion de capillaires perfusés [35] Adrénaline -Crossing-over en addition de dobutamine-noradrénaline, diminution du pH muqueux, du flux splanchnique augmentation du lactate dans la veine hépatique (Meier-Hellmann 1997) En effet, certaines études ont porté sur la microcirculation splanchnique (jéjunale, iléale ou colique), le plus souvent par doppler laser ou vidéomicroscopie (débit, densité capillaire fonctionnelle, hétérogénéité) [42][43][44]. D'autres études ont mesuré l'oxygénation microcirculatoire (StO 2 , HbO 2 ou gradient PO 2 muqueuse/PO 2 artérielle) de la muqueuse et de la sous-muqueuse intestinale par électrodes dédiées [45].…”
Section: Sepsis Périopératoireunclassified